THU0421 Female primary gout had its unique ultrasound features. (15th June 2017) - Lin, DF; Guo, X; Cao, J; Wu, Y; Gu, J
Abstract : Background: Primary gout is a metabolic disease occurred in male and post-menopause female in most cases. Though the ultrasound features of gout had been discovered for several years, no reports illuminated whether there would be difference presentations between different genders in the joints. Objectives: We employed ultrasound instead of dual-energy CT to explore more refined pathological manifestations of primary gout in different genders. Methods: All cases were confirmed as gout fulfilling 1997 ACR classification criteria. All cases excluded secondary gout induced by drug, tumor, hypertension, diabetes mellitus, renal failure. Ultrasound was performed during chronic stage of gout but not at acute attack. The process was done by 2 observers blinded to each other, blood tests. Final diagnosis was determined by the third US expert if the 2 observers got the different conclusion. Bilateral toes, dorsal feet, ankle, knee, wrist, fingers, elbow, and shoulder were detected to find 6 features of gout suggested by OMERCT: tophus, "snow storm"-like effusion, cloudy synovium in grey scale, double-contour sign, bone erosion and Power Doppler (PD) signal. Each above positive presentations in each above range would get 1 point and the sum scores would be ranged from 0 to 84. Serum uric acid (UA) was recorded too. Results: 1) 23 female and 139 male were recruited in the program. The female-male ratio was 1:6. Mean age and disease duration of the female subjects were elder than male ones (female:male=57.2±14.1: 44.7±14.7 years old) with longer disease duration to confim the diagnosis (female:male = 10.9:1.2 months). The average serum UA level in female was lower than male group (female:male = 413.8±162.1umol/L, 515.5±156.9umol/L, sig<0.05). 2) The intra-observer reliability from 20% samples random seclection showed an overall agreement of 80%, 92%, 96%, 87%, 80%, 73% for tophus, "snow storm"-like effusion, cloudy synovium in grey scale, positive double-contour sign, bone erosion and PD signal with kappa value of 0.78, 0. 92, 0.95, 0.86, 0.79, 0.72, respectively. 3) The difference showed female gout had higher frequency of tophus, bone erosion and lower frequency of effusion while the other indexes were equal:topus scores (female:male=87%:, 74.1%), cloudy synovium grey scale scores (female:male=65.2%:62.6%), effusion scores (female:male=17.4%, 31.7%), bone erosion scores (female:male=30.4%, 16.5%), power dopplar scores (female:male=34.8%, 41%), positive double-contour signs (60.9%:59.9%. The top 2 affected ranges were ankle (female:male=69.6%:55.3%), knee (female:mlae=60.9%:54.0%). Furthermore, female gout had more frequently occurred not in the less typical ranges such as fingers (female:male=34.7%:19.4%), elbow (8.7%:2.7%), which might be the cause for delayed diagnosis. Conclusions: Though the level of serum UA was lower, Female gout had its unique ultrasound features with more tophus, bone erosion and less effusion compared to male gout. The less typical ranges were recommended for US examinations. Disclosure of Interest: None declared